Realist Strategies of Republican Peace Niebuhr, Morgenthau, and the Politics of Patriotic Dissent - Tjalve, V. (The Palgrave Macmillan History of International Thought, 2008)
This book's central claim is that Niebuhr and Morgenthau may be read as heirs to a particularly American republicanism, whose ideal of patriotism as "embedded dissent" is a powerful and much-needed corrective to contemporary vocabularies of international justice, legitimacy, and restraint on both the left and the right.